Does Customer Perceived Value Sway Customer Satisfaction and Post Purchase Intentions? Evidence from Online Shopping in Malaysia - Arman Hj. Ahmad; Yuvasreetharan Muregesu; Ridzuan Masri; Mohd Farid Shamsudin; Mohd Faizun Mohamad Yazid (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to measure the impact of Customer Perceived Value (CPV) on Customer Satisfaction and Purchase Intentions in Online Shopping. Three main variables were studied in this paper, namely CPV, customer satisfaction, and online shopping purchase intentions. These variables are not new and have been used in numerous previous research; however, not all relationships were measured together, making this paper distinctive. This study will also provide value for future research done for the customers, merchants, and researchers. This is a quantitative study; thus, questionnaires were used as a means to collect data. Questionnaires were distributed among 500 target respondents among the gen Z, but only 380 were returns. The result revealed that CPV, customer satisfaction, and customer purchase intentions are interrelated. Results indicate that CPV has a positive effect on customer satisfaction and purchase intention. Overall, business needs to focus on developing the CPV and understanding customer expectations to inculcate positive customer post-purchase intentions. In addition, this paper can be used for future research and add value to the existing similar research around the globe and within Malaysia.